Influence of CaCl2 on Biochemical Composition, Antioxidant and Enzymatic Activity of Apricot at Ambient Storage - Ali, Sartaj; Masud, Tariq; Abbasi, Kashif S.; Mahmood, Talat; Hussain, Ijlal (Pakistan Journal of Nutrition, 2013)
Fresh fruits are increasingly focused in the recent years for their nutritional and health benefits. Research involving simple and safe preservation technologies is at a high demand to satisfy consumer concerns and harvest maximum market potential. The present study was therefore undertaken to assess the response of chemical and bioactive compounds (pH, acidity, ascorbic acid, total phenolics, carotenoids, free radical scavenging capacity and enzyme activity) in apricot under the effect of calcium treatments (1, 2, 3 and 4%) at ambient storage. The results revealed that ascorbic acid, phenolic compounds and carotenoids were least affected in 3 and 2% calcium as compared to control, 1 and 4% CaCl2. Similarly, higher antioxidant capacity and lower enzymatic activity was retained in the same concentrations. Titratable acidity and ascorbic acid decreased in all treatments during storage and higher reduction was observed in control, 1 and 4% as compared to 3 and 2% calcium, respectively. pH, phenolics, carotenoids, antioxidant and enzymatic activity increased initially and it was rapid up to 6th day, followed by a slight decrease during subsequent storage. The overall results demonstrated higher compositional losses in control followed by 1 and 4% calcium treated fruits, while 3 and 2% treatments exerted pronounced effects on keeping quality of apricot during ambient storage up to 12th day.